2008
DOI: 10.1016/j.bbrc.2008.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin reductase-1 knock down does not result in thioredoxin-1 oxidation

Abstract: The active site of thioredoxin-1 (Trx1) is oxidized in cells with increased reactive oxygen species (ROS) and is reduced by thioredoxin reductase-1 (TrxR1). The purpose of the present study was to determine the extent to which the redox state of Trx1 is sensitive to changes in these opposing reactions. Trx1 redox state and ROS generation were measured in cells exposed to the TrxR1 inhibitors aurothioglucose (ATG) and monomethylarsonous acid (MMA(III)) and in cells depleted of TrxR1 activity by siRNA knock down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 31 publications
8
36
0
Order By: Relevance
“…It is likely that ATG will not reach the mitochondria. There was no increase in the production of ROS, as shown in this study and reported previously as well (23). Trx stayed reduced, and cell death did not occur.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…It is likely that ATG will not reach the mitochondria. There was no increase in the production of ROS, as shown in this study and reported previously as well (23). Trx stayed reduced, and cell death did not occur.…”
Section: Discussionsupporting
confidence: 89%
“…As shown in Fig. 2B, in cells without treatment, the redox state of Trx1 was mostly fully reduced (lane 2), in line with previous reports (23,34,35). In contrast, as shown in lane 6, in cells treated with 2 M AF, 40% of the total Trx1 was in the fully reduced form, 36% of the total Trx1 migrated with the Ϫ4 mobility, representing a mixed disulfide intermediate with one active site cysteine as a free thiol and the other involved in a disulfide bond to a substrate.…”
Section: Different Redox Responses In Hela Cellssupporting
confidence: 92%
See 2 more Smart Citations
“…However, naturally occurring mRNAs encoding these isoforms have been described, and overexpression of minigenes encoding these isoforms fused to GFP in cultured cells results in cytosolic accumulation of the fluorescent Txnrd2-GFP fusion proteins (Turanov et al, 2006). Moreover, in vitro, recombinant Txnrd2 can reduce Txn1 (Turanov et al, 2006) and diminution of Txnrd1 activity in cell cultures by RNAi or inhibitory drugs does not lead to Txn1 oxidation (Watson et al, 2008).…”
Section: Alternative Pathways Of Supplying Electrons To Rnrmentioning
confidence: 99%